Las representaciones sociales que los niños construyen en la primera infancia sobre los fenómenos naturales a partir de la literatura infantil - Castrillón Gómez, María Camila (Educación, 2016)
This thesis is about the social representations that children have in their early childhood around natural phenomena, and how we can know it through different strategies that the children´s literature provides. It takes place in two schools from Copacabana, first one is a private school named CE Paso a Paso, and the second one is a public school named IE José Miguel de Restrepo y Puerta.